Hubungan Beberapa Faktor dengan Keluhan Nyeri Punggung Bawah pada Karyawan Kantor - M. Kamali Zaman (STIKes Hang Tuah Pekanbaru, 2014)
The office is the neighborhood where work and must be fulfilled the provisions in the workplace ( health, safety and welfare ). Although the office in general is considered safe, but in it still contain health danger that can lead to serious injury. One form of a nuisance that can arise due to a work environment especially in a work environment office is pain the lower back. Population in this research are employees stikes hang tuah pekanbaru who works as a staff of academic.While a sample in this research is the whole population of which satisfies the criteria as a sample in research. The aim of this research to analyze the relationship of Ergonomic Desk Chair and Posture With Low Back Pain on Office Employees. The research method is Analytic Cross Sectional Study with sampling method and 63 employes as sample. Independent variable of this research is body mass index, age, posture, ergonomic desk chair, working time and working olg. Analysis is doing by univariat, bivariate and multivariate. The result obtained is 3 variables that relationship With Low Back Pain on Office Employees that is, body mass index, age, posture. From multivariate analysis acquired that bad posture the most dominant variable that relationship with Low Back Pain, 40 time having low back pain more than worker that good posture (CI 95% : OR = 40).